Efektifitas Penegakan Undang-Undang No 35 Tahun 2014 Tentang Perubahan Atas Undang-Undang Tahun 2002 Tentang Perlindungan Anak Terkait Kekerasan Terhadap Anak - Husni Thamrin; Adi Wijaya; Fransisca Purna Damayanti (LPPM STIH Awang Long, 2020)
Violence against children is an act of physical, sexual, emotional abuse, or neglect of children. Child abuse can also be defined as any act or series of acts of guardianship or omission by a parent or other caregiver that results in harm, or potential harm, or poses a harmful threat to a child. Children are an investment in the future, the next generation of the Nation, all hopes and ideals hang on their shoulders. Children really need attention and affection from the family. As parents, we may have done violence to children intentionally or unwittingly. Unfortunately, the impact of violence on children can be prolonged and even affect children's attitudes in the future. The author uses the library research method or literature review. This literature review research is conducting research from library books, magazines, journals and articles and sources from the internet that are relevant to the problems discussed.